Pelatihan aplikasi digital pengolahan AUM seri-PTSDL berbasis website bagi guru bimbingan dan konseling SLTA di Sumatera Barat - Ifdil, Ifdil; Fadli, Rima Pratiwi; Sin, Tjung Hauw; Zola, Nilma; Amalianita, Berru; Putri, Yola Eka (Universitas Negeri Padang, 2022)
The rapid development of technology demands that all activities be carried out effectively and efficiently, as well as in the guidance and counseling assessment process, innovation and technology development is needed through the website-based AUM PTSDL series. The purpose of this service is training and developing school counselor skills in using the website-based AUM PTSDL assessment tool. This service is carried out by school counselors who are spread across districts in West Sumatra Province. Data was collected through an online questionnaire using Google From which was then analyzed using JAPS. Based on the results of the school counselor training, they felt very satisfied with the use of processing, appearance, ease of access, how to use the website-based PTSDL series AUM, then participants also felt that the material and practices presented by the resource person as a whole were very relevant. In the future, the website-based AUM PTSDL series product can be improved according to the advice of the school counselor and the cooperation of BK organizations is needed in socializing and promoting the product more broadly and the AUM PTSDL series can be developed with other formats.